2006
DOI: 10.1158/1535-7163.mct-06-0022
|View full text |Cite
|
Sign up to set email alerts
|

Vorinostat, a histone deacetylase inhibitor, enhances the response of human tumor cells to ionizing radiation through prolongation of γ-H2AX foci

Abstract: Vorinostat (suberoylanilide hydroxamic acid) is the prototype of a family of hybrid polar compounds that can induce growth arrest in transformed cells and shows promise for the treatment of cancer. Vorinostat specifically binds to and inhibits the activity of histone deacetylases resulting in acetylation of nucleosomal histones and an activation of gene transcription. Because histone deacetylases modulate chromatin structure and gene expression, both of which can influence radioresponse, this study was designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
178
1
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(198 citation statements)
references
References 36 publications
16
178
1
3
Order By: Relevance
“…The fact that γH2AX foci accumulate in long-term treated cells can indicate that HDACI are able either to down-modulate DNA repair or to cause accumulation of γH2AX foci. [15][16][17] Gene expression profiling also demonstrated that a subset of genes monitoring cell cycle, DNA replication and damage repair are downregulated after HDACI exposure. 17 Taken together, these data serve as evidence that accumulation of senescence-associated γH2AX foci can be a trigger of hyperactivation of pathways involved in cell senescence, as was recently proposed on a mouse model, 18 or its consequence.…”
Section: Waf1mentioning
confidence: 98%
“…The fact that γH2AX foci accumulate in long-term treated cells can indicate that HDACI are able either to down-modulate DNA repair or to cause accumulation of γH2AX foci. [15][16][17] Gene expression profiling also demonstrated that a subset of genes monitoring cell cycle, DNA replication and damage repair are downregulated after HDACI exposure. 17 Taken together, these data serve as evidence that accumulation of senescence-associated γH2AX foci can be a trigger of hyperactivation of pathways involved in cell senescence, as was recently proposed on a mouse model, 18 or its consequence.…”
Section: Waf1mentioning
confidence: 98%
“…In mouse xenograft models, the combination of HDACI treatment (MS-275 [42], valproic acid [43], LBH589 [44], LAQ824 [45]and AN-9 [46]) with radiation therapy, results in a greater delay in tumor growth than that accounted for by a simple additive effect of the corresponding individual treatments. HDAC inhibition by LBH589 [44], TSA [47], depsipeptide [48] and SAHA [49] stabilizes and enhances IR-induced phosphorylated histone H2AX nuclear foci, classical markers of DSBs, suggesting that HDACIs inhibit DSB repair and/or render DNA more susceptible to IR-induced damage. HDACIs facilitate radiation-induced killing in tumor cells and at the same time appear to protect healthy tissues from cutaneous radiation syndrome.…”
Section: Sensitization To Exogenous Dna Damage By Hdacimentioning
confidence: 99%
“…Molecular mechanisms underlying this radiosensitizing potential are not yet fully understood, but can be partially explained by the silencing of DNA-repair genes. The HDAC inhibitor sodium butyrate is reported to aggravate radiation-induced damage and enhance apoptosis by inactivation of repair-related genes, such as Ku70 and Ku86 (Munshi et al, 2006). Similarly, treatment with another HDAC inhibitor, Vorinostat, can prolong the appearance of repair foci identified by phosphorylated Histone 2AX (g-H2AX), which is indicative of reduced repair efficiency and increased radiosensitivity (Munshi et al, 2006).…”
Section: Epigenetic Cancer Therapymentioning
confidence: 99%